1851 Cal. Stat. 360–61, An Act to Reincorporate the City of San Francisco, § 13 - (:unkn) unknown (General Publisher, 1851)
Granted the city of San Francisco authority to regulate houses for the storage of gun-powder and other combustibles.
--
Keywords: GUN POWDER STORAGE